The nature of memory impairment in multiple sclerosis: understanding different patterns over the course of the disease - Gich, Jordi; Salavedra-Pont, Judit; Coll-Martinez, Clàudia; Quintana, Ester; Álvarez-Bravo, Gary; Robles-Cedeño, René; Buxó, Maria; Contreras-Rodriguez, Oren; Ramió-Torrentà, Lluís (Frontiers in Psychology, 2024)
Introduction Memory deficit is one of the most common and severe cognitive impairments in patients with multiple sclerosis and can greatly affect their quality of life. However, there is currently no agreement as to the nature of memory deficit in multiple sclerosis. Methods This cross-sectional study, carried out at the Dr. Josep Trueta and Santa Caterina hospitals in Girona (Spain), was designed to determine the semiology of verbal memory deficit in the different stages of the disease. To this end, a modification of Rey’s verbal auditory test was created by introducing two recognition trials between the five learning trials, thus monitoring what happens in terms of acquisition versus the retrieval of information during the learning phase. Linear regression models were used to evaluate verbal episodic memory performance between-groups adjusting results by age, sex, educational level, and the presence of anxiety and/or depressive symptoms. Results 133 patients with multiple sclerosis, clinically isolated syndrome, and radiologically isolated syndrome and 55 healthy controls aged 18–65 years were assessed. It was observed that the memory processes of multiple sclerosis patients worsen with the progression of the disease. In this respect, patients in pre-diagnostic phases (radiologically isolated syndrome and clinically isolated syndrome) show no differences in verbal episodic memory compared to the healthy controls. Patients in the inflammatory stage (relapsing–remitting multiple sclerosis) show a previously learned information retrieval deficit, while patients in progressive stages (secondary progressive multiple sclerosis and primary progressive multiple sclerosis) do not even correctly acquire information. Discussion These results provide significant information to assist in understanding the nature of memory deficits in multiple sclerosis over the course of the disease. These results are discussed in terms of possible cognitive rehabilitation strategies depending on the evolutive stage and are related to neuropathological mechanisms involved in the progression of the disease.